Groundwater Storage Trends and Their Link to Farmer Suicides in Maharashtra State, India - Chinnasamy, Pennan; Hsu, Minna J.; Agoramoorthy, Govindasamy (Frontiers in Public Health, 2019)
Threats posed by land degradation and desertification continue to destabilize India’s agriculture productivity and food security. The enduring negative environmental consequences of the green revolution that started during the 1960s have further contributed to the depletion of soil nutrients in farmlands through heavy input of chemical fertilizers and pesticides. More than half of India’s population depends on farming. When crop productivity fails, the economically-depressed farmers are unfortunately pushed towards suicide. The news of farmers committing mass suicide in Maharashtra state of India has lately received world attention. Although suicide may involve various psychological, social and economic factors, access to irrigation water remains a contentious matter in the agriculture business. The groundwater (GW) data from government sources are limited and not displayed in the public domain for verification. Hence, this study used the Gravity Recovery and Climate Experiment (GRACE) satellite data to compare farmer suicide rate in Maharashtra with GW storage estimates at broad spatiotemporal scales. The results show significant correlations (r = -0.85, p <0.005) between water storage and suicide rate with time lags of two years. Based on the new findings, this study recommends that the GW status needs to be monitored scientifically across India’s suicide zone. By doing so, the worst case scenarios can be logically predicted well in advance. The government then may have the advantage to mobilize its resources on the ground to implement rapid emergency measures to minimize future farmer suicide cases.